Structure design method of carbon fiber composite engine hood - LI HAIPENG; LIANG CHUNYONG; GE GUANGYUE; LI LELE (2017)
The invention discloses a structure design method of a carbon fiber composite engine hood. The method comprises the steps of establishing a mathematical model for size optimization of the composite engine hood by taking parameters such as the ply angle, the ply thickness and the thickness of a core material of a carbon fiber composite one-layer ply as the design variables during structure optimization and conducting the calculations: (1) the design target: the objective function for the size optimization design of the composite engine hood is to make the engine hood to be minimum in weight; (2) design variables; (3) design constraints; (4) calculation conditions; and (5) optimizing the analysis result. When compared with that before optimization, the composite engine hood after optimization has a weight decrease of about 16%, and is basically unchanged in various performance parameters, wherein the first-order frequency is increased, the maximum displacements under static conditions are increased, the stiffne